Envisioning Global Education in Rwanda: Contributions from Secondary School Teachers - Bosire, Abiud; Correia, Luís Grosso; Coelho, Dalila Pinto (Education Sciences, 2025)
Global education (GE) has become important in education due to heightened global interconnectedness and interdependence, with its incorporation into school materials aimed at preparing learners to navigate global challenges. In implementing GE, teachers are considered critical agents to transform normative GE into knowledge in classrooms. This study examines Rwandese teachers’ knowledge, awareness, and perceptions of challenges they face in implementing GE in schools. In a quantitative design, 208 teachers from 15 participating secondary schools completed a survey. The study findings reveal that the teachers had moderate to high levels of knowledge and awareness of global education, with most of the teachers recognising GE to be important in preparing learners for the future and stated the need to incorporate it within the curriculum in Rwanda. This study underscores the need for teacher training and professional development to enhance GE integration, and the provision of necessary resources and materials to enable the implementation of GE in schools in Rwanda.
CRIS-Team Scopus Importer:2025-06-06
Keywords: competence-based curriculum; global education; Rwanda; teachers